Methods of State Support of Innovative Entrepreneurship. The Example of Rural Tourism - ISKAKOVA, Maral Serikovna; ABENOVA, Maira Khomarovna; DZHANMULDAEVA, Lyazzat Nurgalievna; ZEINULLINA, Aigul Zhumagalievna; TOLYSBAEVA, Marzhan Sovetbekovna; SALZHANOVA, Zaure Abildinovna; ZHANSAGIMOVA, Ayagoz (Journal of Environmental Management and Tourism, 2021)
The relevance of the article is determined by the need to develop the potential of small business for the purpose of an innovative breakthrough in the economy of Kazakhstan. Countries that have been fully engaged in supporting innovative entrepreneurship have become leaders. The problem is that the development of small innovative business is not facilitated by a complex state system of regulation and support that is inadequate to the needs of entrepreneurs. However, this is not the main problem of the development of innovative entrepreneurship, which is presented in the most detail in the study. The directions of increasing the effectiveness of the influence of state support programs on the development of innovative entrepreneurship, which are largely borrowed from the foreign experience of developed countries, have been substantiated. The authors propose not only some ways of innovative development of entrepreneurship in Kazakhstan, which, according to the authors, will accelerate the implementation of the innovation process in rural tourism and in the country as a whole. But they also proposed some features that will help overcome the mental barrier and national traditions, both in Kazakhstan and in the post-Soviet space, since due to the lack of an effective legal framework, the problem of corruption is threatening a social explosion. In addition, during the COVID-19 pandemic, the most affected in a difficult epidemiological situation, such organizations that operate in the field of culture, sports, additional education, tourism, hospitality, etc.